Yin Yang 1 promotes aggressive cell growth in high‐grade breast cancer by directly transactivating kinectin 1. Issue 3 (5th July 2022) - Gao, Lin; Zhou, Wenbin; Xie, Ni; Qiu, Junying; Huang, Jingyi; Zhang, Zhe; Hong, Malin; Xia, Jinquan; Xu, Jing; Zhao, Pan; Fu, Li; Luo, Yuwei; et al.
Abstract: Invasive cancer growth and metastasis account for the poor prognosis of high‐grade breast cancer. Recently, we reported that kinectin 1 (KTN1), a member of the kinesin‐binding protein family, promotes cell invasion of triple‐negative breast cancer and high‐grade breast cancer cells by augmenting the NF‐κB signaling pathway. However, the upstream mechanism regulating KTN1 is unknown. Therefore, this functional study was performed to decipher the regulatory cohort of KTN1 in high‐grade breast cancer. Bioinformatic analysis indicated that transcription factor Yin Yang 1 (YY1) was a potential transactivator of KTN1. High YY1 expression correlated positively with pathological progression and poor prognosis of high‐grade breast cancer. Additionally, YY1 promoted cell invasive growth both in vitro and in vivo, in a KTN1‐dependent manner. Mechanistically, YY1 could transactivate the KTN1 gene promoter. Alternatively, YY1 could directly interact with a co‐factor, DEAD‐box helicase 3 X‐linked (DDX3X), which significantly co‐activated YY1‐mediated transcriptional expression of KTN1. Moreover, DDX3X augmented YY1‐KTN1 signaling‐promoted invasive cell growth of breast cancer. Importantly, overexpression of YY1 enhanced tumor aggressive growth in a mouse breast cancer model. Our findings established a novel DDX3X‐assisted YY1‐KTN1 regulatory axis in breast cancer progression, which could lead to the development novel therapeutic targets for breast cancer. Abstract : Invasive cancer cell growth and metastasis accounts for the poor prognosis of high‐grade breast cancer. The transcription factor Yin Yang 1 (YY1) is upregulated in high‐grade breast cancer. YY1 interacted with DEAD‐box protein (DDX3X) via binding to DDX3X. YY1 transactivated KTN1 gene via direct binding its promoter together with the DDX3X. Herein, our findings established a novel YY1‐assisted DDX3X‐ KTN1 regulatory axis, which would shed some light on the signaling involved in cell invasion and progression in breast cancer and open an avenue in finding novel therapeutic targets for breast cancer.